2010
DOI: 10.1038/nature09344
|View full text |Cite
|
Sign up to set email alerts
|

Warm water vapour in the sooty outflow from a luminous carbon star

Abstract: The detection of circumstellar water vapour around the ageing carbon star IRC +10216 challenged the current understanding of chemistry in old stars, because water was predicted to be almost absent in carbon-rich stars. Several explanations for the water were postulated, including the vaporization of icy bodies (comets or dwarf planets) in orbit around the star, grain surface reactions, and photochemistry in the outer circumstellar envelope. With a single water line detected so far from this one carbon-rich evo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
119
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 38 publications
2
119
0
Order By: Relevance
“…The total H 2 O abundance is then ≈1.2 × 10 −5 placing it in between the values typically determined for M-type AGB stars (Justtanont et al 2005;Maercker et al 2008Maercker et al , 2009Decin et al 2010c) and carbon stars (Melnick et al 2001;Hasegawa et al 2006;Decin et al 2010a;Neufeld et al 2010Neufeld et al , 2011. Justtanont et al (2010) derived a total H 2 O abundance of ≈1.1 × 10 −5 for χ Cyg in excellent agreement with the analysis performed here.…”
Section: Oxygen-bearing Moleculessupporting
confidence: 76%
See 2 more Smart Citations
“…The total H 2 O abundance is then ≈1.2 × 10 −5 placing it in between the values typically determined for M-type AGB stars (Justtanont et al 2005;Maercker et al 2008Maercker et al , 2009Decin et al 2010c) and carbon stars (Melnick et al 2001;Hasegawa et al 2006;Decin et al 2010a;Neufeld et al 2010Neufeld et al , 2011. Justtanont et al (2010) derived a total H 2 O abundance of ≈1.1 × 10 −5 for χ Cyg in excellent agreement with the analysis performed here.…”
Section: Oxygen-bearing Moleculessupporting
confidence: 76%
“…Such H 2 O abundances can be explained by a stellar atmosphere equilibrium chemistry. In contrast, to explain the detection of H 2 O in the extreme carbon star IRC +10216 (Melnick et al 2001;Hasegawa et al 2006), even higher abundances in the carbon star V Cyg (Neufeld et al 2010), and the ubiquitous occurrence of H 2 O in CSEs around carbon stars (Neufeld et al 2011), requires some effective nonequilibrium chemical process (Willacy 2004), the influx of H 2 O through the evaporation of icy-bodies (Melnick et al 2001), or, as recently suggested by Decin et al (2010a), the penetration of interstellar ultraviolet photons deep into a clumpy CSE, thereby affecting the chemistry. A study of the S-type AGB star χ Cyg suggests that this type of stars has an intermidiate circumstellar H 2 O abundance (Justtanont et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, observations of CO emission lines have proven to be a useful tool to describe the mass loss (e.g., Schöier et al 2002;González Delgado et al 2003;Ramstedt et al 2008;De Beck et al 2010;Khouri et al 2014a). Observations of other molecules have led to important insights in the chemistry and structure of AGB CSEs (e.g., González Delgado et al 2003;Schöier et al 2007;Maercker et al 2008Maercker et al , 2009Decin et al 2010a;Cernicharo et al 2010Cernicharo et al , 2011De Beck et al 2012;Justtanont et al 2012;Khouri et al 2014b; Lombaert et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…T he great advances experienced by radioastronomy during recent years have depicted the interstellar medium (ISM) and circumstellar envelopes (CSE) as supporting an active and rich chemistry 1 . In these cosmic regions, both simple molecules, such as H 2 or CO, and complex ones, such as C 60 and polycyclic aromatic hydrocarbons (PAHs), are routinely detected by their characteristic infrared spectrum 2,3 .…”
mentioning
confidence: 99%